Weak overcomes strong in sensory integration: shading warps the disparity field - Aubuchon, Celine; Kemp, Jovan; Vishwanath, Dhanraj; Domini, Fulvio (Proceedings of the Royal Society. B, Biological sciences, 2024)
Human perception is often based on the integration of multiple sensory cues, where more statistically reliable cues are considered to have stronger influence on the percept. For example, in three-dimensional shape perception, binocular disparity is considered the most reliable cue at close distances, while pictorial cues like shading are considered less reliable. In three within-subject experiments, we instead show that shading can override disparity, a result that cannot be explained by its measured reliability, cue vetoing or cue promotion. Observers judged the shape of a disparity surface that was combined with different shading patterns. In all tests, shading altered the perceived shape specified by a strong disparity signal in a way that could not be predicted by standard accounts of three-dimensional perception. We find an example of unaccounted for cue cooperation, where shading becomes strong when it interacts with disparity.